2019
DOI: 10.12659/msm.913057
|View full text |Cite
|
Sign up to set email alerts
|

Both Peripheral Blood and Urinary miR-195-5p, miR-192-3p, miR-328-5p and Their Target Genes PPM1A, RAB1A and BRSK1 May Be Potential Biomarkers for Membranous Nephropathy

Abstract: BackgroundTo identify noninvasive diagnostic biomarkers for membranous nephropathy (MN).Material/MethodsThe mRNA microarray datasets GSE73953 using peripheral blood mononuclear cells (PBMCs) of 8 membranous nephropathy patients and 2 control patients; and microRNAs (miRNA) microarray dataset GSE64306 using urine sediments of 4 membranous nephropathy patients and 6 control patients were downloaded from the Gene Expression Omnibus database. The differentially expressed genes (DEGs) and differentially expressed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Zhang et al revealed the increased expression of urine miR-193a in MGN patients compared to healthy controls, and higher urine miR-193a levels were associated with poor renal survival [ 38 ]. Zhou et al conducted the microarray analysis and reported that serum and urine miR-195-5p, miR-192-3p, miR-328-5p levels and their target genes, PPM1A, RAB1A and BRSK1 may be the potential biomarkers for MGN [ 39 ]. Barbagallo et al analyzed miRNA profile and their target mRNAs from MGN kidney tissues and indicated that let-7a-5p, let-7b-5p, let-7c-5p, let-7d-5p, miR-107, miR-423-5p, miR-516-3p, miR-532-3p and miR-1275 levels were upregulated, and miR-129-3p levels were downregulated in MGN kidney samples compared to unaffected kidney tissues undergoing nephrectomy for renal cancer [ 40 ].…”
Section: Mirnas In Membranous Glomerulonephropathymentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al revealed the increased expression of urine miR-193a in MGN patients compared to healthy controls, and higher urine miR-193a levels were associated with poor renal survival [ 38 ]. Zhou et al conducted the microarray analysis and reported that serum and urine miR-195-5p, miR-192-3p, miR-328-5p levels and their target genes, PPM1A, RAB1A and BRSK1 may be the potential biomarkers for MGN [ 39 ]. Barbagallo et al analyzed miRNA profile and their target mRNAs from MGN kidney tissues and indicated that let-7a-5p, let-7b-5p, let-7c-5p, let-7d-5p, miR-107, miR-423-5p, miR-516-3p, miR-532-3p and miR-1275 levels were upregulated, and miR-129-3p levels were downregulated in MGN kidney samples compared to unaffected kidney tissues undergoing nephrectomy for renal cancer [ 40 ].…”
Section: Mirnas In Membranous Glomerulonephropathymentioning
confidence: 99%
“…In spite of the accumulating evidence, most of these reports only analyzed specific miRNAs and there were only three reports in which comprehensive miRNA analysis by microarray was conducted [ 32 , 39 , 40 ]. In addition, most of these studies analyzing miRNAs have been compared MGN patients to healthy controls, not to other NS diseases, such as MCNS and FSGS, thus these miRNA profile changes might not be directly associated with MGN pathogenesis, but might be the common trend in NS patients.…”
Section: Mirnas In Membranous Glomerulonephropathymentioning
confidence: 99%
“…Many miRNAs play their function in MN by modulating gene expression 11,25,26 . Thus, we hypothesized that CXCL16 may be a potential target gene of miR‐500a‐5p and further participates in the circ_0000524‐mediated function in MN.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs could act as microRNAs (miRNAs) sponges, thus leading to the inhibition of mRNAs in many diseases 7‐10 . Recently, miRNAs have been found to be biomarkers for the diagnosis and development of MN 2,11 . It has been revealed that miR‐500a‐5p inhibits cell growth in human colorectal cancer 12 .…”
Section: Introductionmentioning
confidence: 99%
“…miR-195-5p has also been found to regulate hair follicle inductivity of dermal papilla cells by suppressing the activation of the Wnt/β-Catenin signaling pathway (32). Furthermore, it has been suggested that both peripheral blood and urinary miR-195-5p may be a potential biomarker for membranous nephropathy (33). All of these observations indicated that miR-195-5p is expressed differently under different pathophysiological conditions and that miR-195-5p plays a very important role in regulating cell growth.…”
Section: Introductionmentioning
confidence: 99%